Infusion of freshly isolated autologous bone marrow derived mononuclear cells prevents endotoxin-induced lung injury in an ex-vivo perfused swine model - Rojas, Mauricio (BioMed Central, 2013)
INTRODUCTION: The acute respiratory distress syndrome (ARDS), affects up to 150,000 patients per year in the United States. We and other groups have demonstrated that bone marrow derived mesenchymal stromal stem cells prevent ARDS induced by systemic and local administration of endotoxin (lipopolysaccharide (LPS)) in mice. METHODS: A study was undertaken to determine the effects of the diverse populations of bone marrow derived cells on the pathophysiology of ARDS, using a unique ex-vivo swine preparation, in which only the ventilated lung and the liver are perfused with autologous blood. Six experimental groups were designated as: 1) endotoxin alone, 2) endotoxin + total fresh whole bone marrow nuclear cells (BMC), 3) endotoxin + non-hematopoietic bone marrow cells (CD45 neg), 4) endotoxin + hematopoietic bone marrow cells (CD45 positive), 5) endotoxin + buffy coat and 6) endotoxin + in vitro expanded swine CD45 negative adherent allogeneic bone marrow cells (cultured CD45neg). We measured at different levels the biological consequences of the infusion of the different subsets of cells. The measured parameters were: pulmonary vascular resistance (PVR), gas exchange (PO(2)), lung edema (lung wet/dry weight), gene expression and serum concentrations of the pro-inflammatory cytokines IL-1β, TNF-α and IL-6. RESULTS: Infusion of freshly purified autologous total BMCs, as well as non-hematopoietic CD45(-) bone marrow cells significantly reduced endotoxin-induced pulmonary hypertension and hypoxemia and reduced the lung edema. Also, in the groups that received BMCs and cultured CD45neg we observed a decrease in the levels of IL-1β and TNF-α in plasma. Infusion of hematopoietic CD45(+) bone marrow cells or peripheral blood buffy coat cells did not protect against LPS-induced lung injury. CONCLUSIONS: We conclude that infusion of freshly isolated autologous whole bone marrow cells and the subset of non-hematopoietic cells can suppress the acute humoral and physiologic responses induced by endotoxemia by modulating the inflammatory response, mechanisms that do not involve engraftment or trans-differentiation of the cells. These observations may have important implications for the design of future cell therapies for ARDS.